Dyrektywy sędziowskiej oceny materiału dowodowego w sprawie o nieważność małżeństwa. Glosa do wyroku Roty Rzymskiej c. Salvatori z dnia 6 lipca 2012 r. - Młynarczyk, ks. Adam (Łódzkie Studia Teologiczne, 2024)
This scientific paper is a commentary on a negative sentence of the Tribunal of the Roman Rota about nullity of marriage which supposed to be caused by an exclusion of bonum prolis and bonum sacramenti by a petitioner. The structure of the sentence is unusual because argumentation produced “in iure” contains only few short phrases regarding matrimonial consent as an efficient cause of marriage and totally does not concern the content of expressions “good of offspring” and “good of the Sacrament”. However, the Judge has profoundly analysed the directives of the evaluation of evidence. The section of the sentence, which refers to a factual state, is an outstanding example of a reliable analysis of declarations of the parties and testimonies of witnesses and compares them to all other circumstances of the case. They are aimed at reconstruction of the factual state, as accurately as possible, in order to receive moral certitude which is crucial to pass a sentence.